Two-dimensional and three-dimensional postsurgical temporomandibular joint condylar remodelling following vertical subsigmoid osteotomy setback surgery - Choi, Wing Shan; Subramaniam, Pram Kumar (Elsevier, 2017)
Background: Vertical subsigmoid osteotomy (VSSO) for ramus setback has been suggested to exert less stress onto the condylar head causing more positive bone remodelling changes in the postoperative phase. However, it is unclear if the setback amount has any effect on the remodelling pattern. Objectives: This study aims to compare the postsurgical quantitative and qualitative condylar remodelling changes in various setback magnitudes using two-dimensional (2D) and threedimensional (3D) radiography. Methods: Retrospective pre- and postoperative radiographic data of patients with mandibular prognathism that had undergone VSSO from 2007 to 2012 at the Prince Philip Dental Hospital were traced. 130 postero-anterior and lateral cephalographs, along with 174 cone-beam computed tomography (CBCT) scans were retrieved. 2D and 3D radiographic tracing were performed to measure the condyle-ramal morphometric values. Pre- and postoperative CBCT rendered condyle ramus segments were superimposed based on stable growth registration points to observe zonal and topographic changes. Findings and Conclusion: 2D radiographic tracing did not show significant condyle-ramal changes in different setback magnitudes. 3D radiographic tracing showed significant changes in axial condylar depth with more setback. Topography analysis also showed that in the postero-superior condylar surface, more bone deposition was found in larger setback. In the axial plane, the bone formation proportion at the condylar head was significantly increased in mid-anterior and posteromedial zones with larger setback except in the group with setback between 4.1–6 mm. In general the condylar remodelling pattern after VSSO for mandibular setback was considered to be stable despite various setback magnitudes.